Power of Andrographis paniculata: molecular docking of Andrographolide and its derivatives targeting Interleukin-1 Beta to Treat Anti-inflammation / Mohamad Iman Haikal Che Nor Salahuddin - Che Nor Salahuddin, Mohamad Iman Haikal (2025)
The study revealed the molecular docking of Andrographolide and its derivatives towards Interleukin-1 Beta as a key protein in anti-inflammatory drug design using AutoDock Vina, AMDock and PyMol applications. Among all compounds, CHEMBL4887996 exhibited the highest binding affinity (-8.0 kcal/mol) and stability, followed by andrographolide and its derivatives with scores ranging from -7.3 to -6.8 (kcal/mol). All compounds target the same binding site to form hydrophobic and hydrogen bonds. Therefore, the compound CHEMBL4887996 showed the most stable interaction based on this study. These findings highlight the potential of CHEMBL4887996 as a superior anti-inflammatory agent, especially for treating diabetic patients and optimizing drug design.